Biochar addition augmented the microbial community and aided the digestion of high-loading slaughterhouse waste: Active enzymes of bacteria and archaea. (December 2022) - Guo, Zhaodi; Jalalah, Mohammed; Alsareii, Saeed A.; Harraz, Farid A.; Thakur, Nandini; Salama, El-Sayed
Abstract: The biogas production (BP), volatile fatty acids (VFAs), microbial communities, and microbes' active enzymes were studied upon the addition of biochar (0–1.5%) at 6% and 8% slaughterhouse waste (SHW) loadings. The 0.5% biochar enhanced BP by 1.5- and 1.6-folds in 6% and 8% SHW-loaded reactors, respectively. Increasing the biochar up to 1.5% caused a reduction in BP at 6% SHW. However, the BP from 8% of SHW was enhanced by 1.4-folds at 1.5% biochar. The VFAs production in all 0.5% biochar amended reactors was highly significant compared to control ( p- value < 0.05). The biochar addition increased the bacterial and archaeal diversity at both 6% and 8% SHW loadings. The highest number of OTUs at 0.5% biochar were 567 and 525 in 6% and 8% SHW, respectively. Biochar prompted the Clostridium abundance and increased the lyases and transaminases involved in the degradation of lipids and protein, respectively. Biochar addition improved the Methanosaeta and Methanosphaera abundance in which the major enzymes were reductase and hydrogenase. The archaeal enzymes showed mixed acetoclastic and hydrogenotrophic methanogenesis. Graphical abstract: Image 1 Highlights: Maximum biogas production in all SHW loadings was achieved at 0.5% biochar. The core microbes in all reactors were Clostridium (>45%) and Methanosaeta (>40%). Lyases and transaminases were the major bacterial enzymes for SHW-digestion. Reductase and hydrogenase were the core archaeal enzymes for biogas production.